CONCEPT OF DEVELOPMENT OF THE ASTANA BOTANICAL GARDEN - G.Т. Sitpayeva (Academic Journal of Physical and Chemical Sciences, 2019)
To date, the steppe ecosystems of the Republic lacked research institutions that develop theoretical and applied issues of introduction and green construction in the region. The basis for the design of the Botanical garden in the territory of Northern Kazakhstan was the Protocol of the meeting with the participation of the First President of Kazakhstan N. A. Nazarbayev on April 11, 2012. In 2012, the RSE on the ECC "Institute of Botany and Phytointroduction" of the SC at Kazakh MSE presented a natural-scientific justification for the creation of a Botanical garden in Nur-Sultan. The official opening ceremony of the Astana Botanical garden with the participation of the First President of Kazakhstan N. A. Nazarbayev was held on July 2, 2018. In accordance with the Law "On protected areas" of Kazakhstan (2006), the main activities of the state botanical gardens is the development of scientific fundamentals of preservation, reproduction and use of fauna of Kazakhstan, development of the flora of Kazakhstan, of global significance [article 58]. State Botanical gardens are used in accordance with the established procedure for scientific, cultural, educational and educational purposes. The developed Concept of development of Nur-Sultan Botanical Garden of is aimed at laying the foundations for its development as a multifunctional leading research, educational, cultural, educational and environmental institution in Northern and Central Kazakhstan. Botanical Garden of our capital should become a testing ground and demonstration of "green technologies", technologies of preservation of the genetic Fund of plants, modern agricultural technologies, training technologies and "mass media" propaganda. The studies formulated the concept of development of Nur-Sultan Botanical Garden, set objectives, direction and prospects of the Botanical Garden in Nur-Sultan in accordance with the Law "On protected areas" of Kazakhstan (2006), while illustrating effective ways in implementing educational, cultural and social activities.